2020
DOI: 10.1088/1757-899x/823/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa oleifera leaf powder in diets on laying hens performance, β-carotene, cholesterol, and minerals contents in egg yolk

Abstract: The present study was designed to investigate the influence of Moringa oleifera on Laying Hens Performance, β-carotene, cholesterol, and minerals contents in egg yolk. Two hundred and forty 30 weeks of healthy laying hens with homogeneous body weight in a complete randomized design with four treatments and 6 replications. Laying hens were randomly divided into four groups: M0: diets without administration of Moringa oleifera leaves, M1: diets with 2% Moringa oleifera leaves; M2: diets with Moringa oleifera lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 44 publications
1
15
1
3
Order By: Relevance
“…This was because the nutritional content of the rations of roles layer tife was the same in each treatment given sugar apple leaf extract and not given as a control. This is in line with the opinion of Bidura et al (2020), that the administration of herbal extracts (katuk leaves and garlic) as much as 5 cc/100 cc of drinking water did not significantly affect the consumption of rations. Authority (2016), also reported that the administration of plant herbal extracts (garlic) through drinking water at a concentration of 2.5-5% had no significant effect on ration consumption.…”
Section: Performance Of Roles Layer Tifesupporting
confidence: 91%
“…This was because the nutritional content of the rations of roles layer tife was the same in each treatment given sugar apple leaf extract and not given as a control. This is in line with the opinion of Bidura et al (2020), that the administration of herbal extracts (katuk leaves and garlic) as much as 5 cc/100 cc of drinking water did not significantly affect the consumption of rations. Authority (2016), also reported that the administration of plant herbal extracts (garlic) through drinking water at a concentration of 2.5-5% had no significant effect on ration consumption.…”
Section: Performance Of Roles Layer Tifesupporting
confidence: 91%
“…Since the high cholesterol content in egg yolks is an inhibiting factor for consumers, reducing cholesterol in egg yolks will benefit the poultry industry and public health [ 18 , 32 ]. Thus, in this study, the second functional egg property monitored was the potential decrease of cholesterol content in egg yolks during the 8-week feeding trial.…”
Section: Discussionmentioning
confidence: 99%
“…While the hen feed supplementation with DML has been largely described for its cholesterol-lowering effects, less documented is the effect of the goji berry supplementation on cholesterol content in egg yolks. In this regard, Bidura et al reported that the fortification of hen feed with DML led to the production of eggs with a significantly lower cholesterol level in the egg yolk [ 18 ]. A supplementation of Moringa leaves may reduce the cholesterol content of egg yolks in two possible ways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations